A STUDY OF DISCOURSE MARKERS USED IN THE THESES BACKGROUND WRITTEN BY THE STUDENTS OF ENGLISH DEPARTMENT OF BENGKULU UNIVERSITY (ACADEMIC YEAR DECEMBER 2016) - Dio Adewibowo; Imranuddin .; Azwandi . (Journal of English Education and Teaching, 2018)
This research was aimed at finding the types of Discourse Markers used by the students and investigating the accuracy of Discourse Markers by the students of English Education Study program graduated in December 2016 at the University of Bengkulu. This research was a descriptive study. The subjects in this research were 10 theses background from the students of English Education Study Program who graduated in December 2016. The result of this research shows that there were four types of Discourse Markers used by the students based on Bruce Fraser’s theory such as Inferential markers, temporal markers, elaborative markers and contrastive markers. The most dominant marker used by the students was Inferential markers with 42%. This research also found that the most accurate marker used was Temporal markers with 78.57% and the lowest accurate marker was Elaborative markers with 52.17%.